Ciliopathies: Coloring outside of the lines. Issue 3 (25th December 2020) - Strong, Alanna; Li, Dong; Mentch, Frank; Bedoukian, Emma; Hartung, Erum A.; Meyers, Kevin; Skraban, Cara; Wen, Jessica; Medne, Livija; Glessner, Joseph; Watson, Deborah; Krantz, Ian; et al.
Abstract: Ciliopathy syndromes are a diverse spectrum of disease characterized by a combination of cystic kidney disease, hepatobiliary disease, retinopathy, skeletal dysplasia, developmental delay, and brain malformations. Though generally divided into distinct disease categories based on the pattern of system involvement, ciliopathy syndromes are known to display certain phenotypic overlap. We performed next‐generation sequencing panel testing, clinical exome sequencing, and research‐based exome sequencing reanalysis on patients with suspected ciliopathy syndromes with additional features. We identified biallelic pathogenic variants in BBS1 in a child with features of cranioectodermal dysplasia, and biallelic variants in BBS12 in a child with the clinical stigmata of Bardet‐Biedl syndrome, but also with anal atresia. We additionally identified biallelic pathogenic variants in WDR35 and DYNC2H1 in children with predominant liver disease and ductal plate malformation without skeletal dysplasia. Our study highlights the phenotypic and genetic diversity of ciliopathy syndromes, the importance of considering ciliopathy syndromes as a disease‐spectrum and screening for all associated complications in all patients, and describes exclusive extra‐skeletal manifestations in two classical skeletal dysplasia syndromes.